Meaningful Arrangement : Exploring the Syntactic Description of Texts. - MacDonald, E. (Edward) (Functional linguistics., 2008)
This book takes apart and problematises the whole process of identifying and explaining the patterning of words in sentences. It brings together two concepts - syntax and text - that are normally treated separately, and shows how they can best be understood in relation to each other.